2006
DOI: 10.1063/1.2201767
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic levitation of superconducting bars

Abstract: Levitation force is studied in a two-dimensional system consisting of an infinitely long superconductor immersed in the magnetic field created by different arrangements of infinitely long parallel permanent magnets, based on the critical-state model using the magnetic energy minimization procedure. Results on force, stability, and losses in the levitation process in this system are analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 30 publications
0
33
0
Order By: Relevance
“…However, the functional F SC J; r ½ cannot be considered as simply the energy of the system (SC), because it describes a hysteretic process given by the constraint jJj J c . F SC J; r ½ reduces to the functional introduced by Prigozhin 28,29 and that we have widely used 26,27,30 if the interaction with the FM is not considered; under some conditions 27 this functional is equivalent to the magnetic energy.…”
Section: Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the functional F SC J; r ½ cannot be considered as simply the energy of the system (SC), because it describes a hysteretic process given by the constraint jJj J c . F SC J; r ½ reduces to the functional introduced by Prigozhin 28,29 and that we have widely used 26,27,30 if the interaction with the FM is not considered; under some conditions 27 this functional is equivalent to the magnetic energy.…”
Section: Modelingmentioning
confidence: 99%
“…a) The model we present will allow the simultaneous calculations of the current profiles in the SC, which is assumed to be in the critical state with constant critical-current density, J c , 23 and the magnetic pole density in the FM that assumes infinite susceptibility and non hysteretic magnetization by minimization of a functional related with the magnetic energy. We introduced similar models based on minimization methods earlier, although the minimization process was only applied to the superconducting part [24][25][26] or the soft magnetic part. 14 This paper is structured as follows.…”
mentioning
confidence: 99%
“…͑1͒ in Ref. 15, with the constraints that the net current must be zero and the current density does not exceed the J c . Introducing the J c ͑H i ͒ dependence by means of a first-order iterative algorithm, it is found that, following the notation of Prigozhin, 16 minimizing this functional with the current density J is equivalent to minimizing a functional FЈ with the current density variation ␦J defined as the difference, at present field H, between the present current density J͑r , H͒ and the previous current density Ĵ͑r , H͒ ͑at the first step of H a , Ĵ͑r , H͒ is assumed zero͒.…”
Section: Tunability Of the Critical-current Density In Superconductormentioning
confidence: 99%
“…The values of the levitation forces that have been presented are needed complement to the design studies for any superconducting magnetic transportation systems (MAGLEV) [5,6]. The present measurements are preliminary to judge on the future possibility to use MgB 2 bulk superconductors in the transportation sector.…”
Section: Discussionmentioning
confidence: 99%